2020
DOI: 10.1021/acs.macromol.0c00193
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Mobility–Stretchability Relationship of Ester-Substituted Polythiophene Derivatives

Abstract: Poly(3-hexylthiophene) (P3HT) has been one of the most important organic semiconductors in the past few decades. To date, considerable effort has been dedicated toward improving its charge mobility, air sensitivity, and even stretchability. In this work, through a systematic investigation, the estersubstituted side chain is manifested to effectively improve the charge mobility, air stability, and stretchability of polythiophenes. Herein, three series of polythiophenes with different side chains and backbones a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Polythiophenes are the most widely investigated π‐conjugated semiconducting polymers, which exhibit tunable as well as effective conjugation lengths and HOMO–LUMO gaps. [ 28 ] Therefore, polythiophenes present high charge mobility (up to 0.41 cm 2 V −1 s −1 ) [ 29 ] and are utilized for a variety of applications in (opto)electronics.…”
Section: Molecular Structures That Exhibit Ultralow Attenuation Coeffmentioning
confidence: 99%
“…Polythiophenes are the most widely investigated π‐conjugated semiconducting polymers, which exhibit tunable as well as effective conjugation lengths and HOMO–LUMO gaps. [ 28 ] Therefore, polythiophenes present high charge mobility (up to 0.41 cm 2 V −1 s −1 ) [ 29 ] and are utilized for a variety of applications in (opto)electronics.…”
Section: Molecular Structures That Exhibit Ultralow Attenuation Coeffmentioning
confidence: 99%
“…Generally, the conjugated polymers possess heterogeneous structures with rigid backbones and flexible side chains, where the backbones determinate the optoelectronic properties, and the flexible side chains increase the solubility in processing solvents . Thus, different molecular design strategies can be employed to balance the mechanical and electrical properties of conjugated polymers, that is, preparing triblock copolymers with soft building blocks, partially breaking the conjugation in backbones, and incorporating long flexible side chains or self-healed cross-linking moieties. , These strategies have greatly improved the ductility of conjugated polymers without significantly decreasing the charge mobility (Table ). For example, Bao et al successfully fabricated intrinsically stretchable conjugated polymer films with high mobility of 1.12 cm 2 V –1 s –1 at 100% strain by introducing alkyl spacers with hydrogen-bonding moiety into backbones of conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…These side chains could significantly impact the mechanical properties of the resulting conjugated polymers since the flexible side chains disperse energy under stress and protect the main chains. Many reports have indicated that the mechanical properties of conjugated polymers can be improved by varying the length, , size, , branched point, and grafted density of the side chains. Additionally, many new side chains have been designed and developed to improve the stretchability of conjugated polymers, including carbosilane, , alkyl-thienyl, poly­(butyl acrylate), and poly­(acrylate amide) …”
Section: Introductionmentioning
confidence: 99%